Hyperbaric hyperoxia exposure in suppressing human immunodeficiency virus replication: An experimental in vitro in peripheral mononuclear blood cells culture - Budiarti, Retno (Infect Dis Rep, 2020)
Cellular immune has an important role in response HIV infection, which is attack the infected cells to activate signaling molecule. Hyperbaric Oxygen (HBO) worked as complementary treatment for HIV infection. The production of ROS and RNS molecules during hyperbaric exposure can affect gene expression which contributes to cellular adaptative response. This study was conducted to explore the mechanisms of cellular adaptive response to HIV infection during hyperbaric exposure. This study was carried on in vitro using healthy volunteers’ PBMCs (Peripheral Blood Mononuclear Cells) cultures infected with HIV-1. The study was conducted as a posttest only group design. The experimental unit was PBMC from venous blood of healthy volunteers which were cultured in vitro and infected by co-culturing with HIV- 1 in MT4 cell line. The experimental unit consist of treatment and control group. Each group examined the expression of transcription factor NFκB, Interferon α, reverse transcriptase inhibitors (p21), and the amount of HIV-1 p24 antigen. There were increasingly significant differences in the expression of the trancription factor of NFκB, p21, andHIV-1 p24 antigen,as well as mRNA transcription of interferon α2 between treatment and controlgroup. By decreasing p24 antigen showed that HBO exposure was able to suppress HIV-1 replication. The exposure to hyperbaric oxygen at the pressure of 2.4 ATAand 98% oxygen wasable to produce ROS and RNS molecules, which play a role in cellular adaptive responses through increasing the expression of nfĸb, p21 and mRNA of interferon α2 plays a role in inhibition mechanism of HIV-1 replication in cells.